Cerebral aspergillosis within new tumour site presents as incidental new brain lesion in patient receiving temozolomide for glioblastoma multiforme. Issue 5 (31st May 2019) - Liu, Shiyuan Anabeth; Sullivan, Timothy; Bryce, Clare; Chan, Amy M; Cilmi, Salvatore
Abstract : Glioblastoma multiforme (GBM) is an aggressive tumour that can lead to lymphopaenia. Its standard treatment involves temozolomide (TMZ) chemotherapy with radiation, often with addition of corticosteroids for symptomatic management. Although TMZ is also immunosuppressive, patients receiving TMZ rarely develop disseminated opportunistic infections. Here, we report the case of a patient with GBM receiving TMZ, radiotherapy and corticosteroids, who develops an incidental new brain lesion that is found to be disseminated Aspergillus within a new GBM tumour site. The patient received successful early treatment of her central nervous system aspergillosis. This case illustrates the profound immunosuppressive potential of GBM in conjunction with TMZ and corticosteroids, which can lead to high-morbidity opportunistic infections concurrently with tumour progression. Future research is needed to elucidate GBM, TMZ and corticosteroids' compound immune effects and guide management that strikes a balance between treating high-morbidity infections and continuing with immunosuppressive chemotherapy.